Quadriceps Muscle Geometry and Strength Throughout Maturation in National-Level Male Soccer Players: A Cross-Sectional Study [Letter] - Bordoni B (Open Access Journal of Sports Medicine)
Bruno Bordoni Dipartimento di Cardiologia, Fondazione Don Carlo Gnocchi IRCCS, Istituto di Ricovero e Cura, S Maria Nascente, Milano, 20100, ItalyCorrespondence: Bruno Bordoni, Email bordonibruno@hotmail.com, bbordoni@dongnocchi.it